ANALISIS TENTANG PERGESERAN PERAN SERTA MASYARAKAT ADAT MINANGKABAU DALAM PENYELESAIAN TINDAK PIDANA PERZINAAN DENGAN DIKELUARKANNYA UNDANG-UNDANG NOMOR 1 TAHUN 2023 - Nofrizal Nofrizal; Wendra Yunaldi (Yustitia, 2025)
Law Number 1 of 2023 concerning the Criminal Code (KUHP) as a replacement for the Dutch Criminal Code has been passed and is currently undergoing a socialization period until 2026. The new Criminal Code, which is considered to be in accordance with the character of the Indonesian nation's spirit, is still reaping pros and cons among society. The expansion of the principle of legality by accommodating existing laws in society and Article 411 concerning adultery has become a polemic among society, especially the Minangkabau indigenous community. According to the beliefs of the Minangkabau indigenous people, the benchmark for the act of adultery is not only the presence of sexual intercourse outside of marriage, but more so the presence of moral norms that are violated by the perpetrator. Article 411, which is an absolute complaint offense, indirectly closes the role of the Minangkabau indigenous community in eradicating and resolving adultery cases. The Nan Salapan Law, which is the basis for enforcing Minangkabau customary criminal law, is overridden by the national criminal law because as long as an act has been regulated in the national Criminal Code, the laws that exist in society can no longer be applied. This research uses normative research methods, namely research that focuses on statutory regulations or research based on norms that apply in society.